2020
DOI: 10.1126/science.abb4255
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of a systemic STING-activating non-nucleotide cGAMP mimetic

Abstract: Stimulator of interferon genes (STING) links innate immunity to biological processes ranging from antitumor immunity to microbiome homeostasis. Mechanistic understanding of the anticancer potential for STING receptor activation is currently limited by metabolic instability of the natural cyclic dinucleotide (CDN) ligands. From a pathway-targeted cell-based screen, we identified a non-nucleotide, small-molecule STING agonist, termed SR-717, that demonstrates broad interspecies and interallelic specificity. A 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
251
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(261 citation statements)
references
References 34 publications
10
251
0
Order By: Relevance
“…As a consequence of genomic insults occurring early in the course of oncogenesis, DNA fragments translocate to the cytoplasm, providing a cellular ''danger signal'' (Dhanwani et al, 2018;Paludan and Bowie, 2013;Won and Bakhoum, 2020). Cytoplasmic DNA sensing and downstream response are critical for anticancer immune responses and have generated excitement as a potential therapeutic opportunity (Chin et al, 2020;Pan et al, 2020). The cytoplasmic DNA sensor is now understood to be a condensate that forms in response to this cellular stress.…”
Section: Revisiting Mechanisms In Common Oncogenic Eventsmentioning
confidence: 99%
“…As a consequence of genomic insults occurring early in the course of oncogenesis, DNA fragments translocate to the cytoplasm, providing a cellular ''danger signal'' (Dhanwani et al, 2018;Paludan and Bowie, 2013;Won and Bakhoum, 2020). Cytoplasmic DNA sensing and downstream response are critical for anticancer immune responses and have generated excitement as a potential therapeutic opportunity (Chin et al, 2020;Pan et al, 2020). The cytoplasmic DNA sensor is now understood to be a condensate that forms in response to this cellular stress.…”
Section: Revisiting Mechanisms In Common Oncogenic Eventsmentioning
confidence: 99%
“…This work has demonstrated that intratumoral activation of the proinflammatory STING pathway by PARP inhibitors is amplified by synthetic cyclic dinucleotide agonists of STING, leading to robust and durable anti-tumor immune responses in BRCA1-mutant TNBC models. It will be important to extend these findings to other tumor models and to determine whether similar results can be achieved with systemic agonists of STING, currently under development (19,20). In conclusion, the potent preclinical therapeutic efficacy of combined PARP inhibition and STING agonism warrants further development of this regimen as a treatment for BRCA-associated TNBC.…”
Section: Resultsmentioning
confidence: 89%
“…Recent studies reported by Pan et al 138 . and Chin et al 139 . have demonstrated promising results in preclinical models.…”
Section: Targeting the Tmementioning
confidence: 96%